# How to solve the cubic equation $x^3-12x+16=0$ [closed]

Please help me for solving this equation $x^3-12x+16=0$

-

## closed as off-topic by Live Forever, Jack D'Aurizio, J. W. Perry, Claude Leibovici, Eric StuckyAug 6 '14 at 8:30

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Live Forever, Jack D'Aurizio, J. W. Perry, Claude Leibovici, Eric Stucky
If this question can be reworded to fit the rules in the help center, please edit the question.

What have you tried? Hint: Using factor theorem, find a zero of given polynomial. Note that any rational root must be a factor of $16$ . – TheJoker Oct 6 '12 at 13:21

This is a cubic equation. The forme of cubic equation is $x^3+px+q=0$ where

$1)$ $p$, $q$ $\in$ R

$2)$ $D=(\frac{q}{2})^2+(\frac{p}{3})^3$

$3)$ $x=u+v=\sqrt[3]{-\frac{q}{2}+\sqrt{(\frac{q}{2})^2 +(\frac{p}{3})^3}}+\sqrt[3]{-\frac{q}{2}-\sqrt{(\frac{q}{2})^2 +(\frac{p}{3})^3}}$

For the given equation we have:

$p=-12$, $q=16$, $D=(\frac{16}{2})^2+(\frac{-12}{3})^3=8^2+(-4)^3=64-64=0$.

Because $D=0$, $u=v=\sqrt[3]{\frac{-q}{2}}$ $\Rightarrow$ $u=v=\sqrt[3]{\frac{-16}{2}}=\sqrt[3]{-8}$ $\Rightarrow$ $u_1=v_1=-2$.

Definitly

$x_1=2u_1$ $\Rightarrow$ $x_1=-4$

$x_2=x_3=-u_1$ $\Rightarrow$ $x_2=x_3=2$

-
This's too complicated... – ᴊ ᴀ s ᴏ ɴ Oct 6 '12 at 13:24
@jasoncube Maybe, but is gives you the general way to solve these type of cubics, even when you can't use the factor theorem of find roots by inspection. I think it is worth learning. – Pedro Tamaroff Oct 6 '12 at 13:32

HINT:

\begin{align*} x^3-12x-16&=x\underbrace{(x^2-4)}_{(x-2)(x+2)}-8x-16 \tag{1}\\ &=x(x-2)(x+2)-\underbrace{8x-16}_{-8(x+2)}\\ &=(x+2) \underbrace{(x^2-2x-8)}_{\text{quadratic equation}}=0 \\ \end{align*}

Now just solve the quadratic equation and you should get something like: $$(x+2)(x+a)(x+b)=0\tag{2}$$ and find: $\,\,x=-2,x=-a \,\,\text{or}\,\,x=-b$

-

Can you see by inspection that 2 is a root? If so, we can write your equation as $x^{3}-12x+16=(x-2)(ax^2+bx+c)=ax^{3}+(b-2a)x^{2}+(c-2b)x-2c$ by the factor theorem. Thus, $a=1$, $b-2a=0$, $c-2b=-12$ and $-2c=16$
Which gives $a=1$, $b=2$ and $c=-8$.
Therefore $x^{3}-12x+16=(x-2)(x^2+2x-8)=(x-2)(x-2)(x+4)=(x-2)^{2}(x+4)$
So there is a repeated root at $x=2$ and a second at $x=-4$.

-

Hint: $x=2$ is a solution of the polynomial.

So $x^3-12x+16$ is divisible by $(x-2)$.

And $x^3-12x+16= (x-2)(x^2+2x-8)$.

The roots of $x^3-12x+16=0$ are $x=2$ and the roots of $x^2+2x-8=0$.

-

HINT: Since $$(s-t)^3+3st(s-t)+s^3-t^3=0$$ Thus, if you could find $s,t$ such that $s^3-t^3=16$ and $3st=-12$ then $x=s-t$ is a root.

EDIT: Taking $3st=-12\implies t=-\frac{4}{s}$ and putting it int equation $s^3-t^3=16\implies s^3-(\frac{-64}{s^3})=16$ Now let $y=s^3$ which converts it into quadratic equation in $y$ and you can solve it and then $s=y^{1/3}$. after getting $s$, compute corresponding $t$ and then $x=s-t$ is a root of the given equation.

In this particular equation $x=2$ satisfies the equation. Now to find other two roots divide $x^3-12x+16$ by $x-2$ to get a quadratic equation and solve it to get other roots

-